Incidencia de teletrabajo en el Desarrollo de las Medianas Empresas de la Ciudad de Loja - Macas Pacheco, Yoselin Mishell (2024)
The present research aims to determine the "Incidence of telework in the development of medium-sized enterprises in the city of Loja", which applied a descriptive non- experimental-explanatory approach based on a qualitative-quantitative study, allowing to obtain information from the managers of the different companies under study as well as their workers and employees, the descriptive non-experimental method was helpful to detail certain characteristics of telework and medium-sized enterprises, the technique used was the application of surveys as it allowed the collection of relevant information for research. As a result it was determined the number of companies that applied telework within their facilities, the advantages and disadvantages for both the company and for workers and employees of which within the benefits highlights the reduction of infrastructure costs, savings and maximization of resources, flexibility of schedules, autonomy in the development of activities, on the other hand with regard to the disadvantages is the little or no supervision of workers, difficulty in motivating them, physical and psychological problems, ect. The incidence of telework varies depending on the activity to which each of the companies is dedicated, this will be taken either positively or negatively depending on the results obtained by each of them. In the case of the present research, teleworking allowed the development of medium-sized companies in various aspects, both administrative and economic.